Dialogic teacher training. Re-enchantment with the teaching profession (Journal of Parents and Teachers, 2016)
Dialogic training can overcome some of the most important challenges of teacher training in Spain: the promotion of more democratic models which are adjusted to criteria of scientific and human quality, in order to maximize their impact on improving students training.
Keywords: Teacher training; dialogic pedagogic gathering; dialogic learning; scientific evidence; dialogical construction of knowledge.